Robust O-Pd-Cl catalyst-electrolyte interfaces enhance CO tolerance of Pd/C catalyst for stable CO2 electroreduction. (15th December 2022) - Tan, Xinyi; Yu, Chang; Song, Xuedan; Ni, Li; Xu, Hanyu; Xie, Yuanyang; Wang, Zhao; Cui, Song; Ren, Yongwen; Li, Wenbin; Zhang, Yafang; Qiu, Jieshan
Abstract: Carbon-supported Pd catalysts are highly active yet can be easily poisoned by the in-situ formed carbon monoxide (CO) during CO2 electrochemical reduction reaction (CO2 RR). Herein, we introduce a novel approach to enhance the CO tolerance and activity of Pd/C catalyst by manipulating catalyst-electrolyte interfaces in saturated KCl electrolyte. During the CO2 RR, the Cl - ions in electrolyte trigger the surface dynamic reconstruction of Pd/C catalyst with the formation of O-Pd-Cl species at catalyst-electrolyte interfaces. The reconstructed Pd/C catalysts can achieve nearly 100% of CO Faradaic efficiency and feature high stability and CO tolerance, which can maintain a better activity in the presence of over 2000 ppm and 23200 ppm of CO in H-type cell and flow cell, respectively. Meanwhile, using such highly concentrated electrolyte, the hydrogen evolution reaction is strongly suppressed. The experimental and theoretical results have confirmed that the O-Pd-Cl species mediated by Cl - ions enable the high activity, good CO resistance and long lifetime of the Pd/C catalyst. These findings may provide some inspirations into the design and fabrication of active yet stable Pd-based catalysts for CO2 electroreduction, and offer some insights into manipulation of the activity and stability for the Pd catalysts at catalyst-electrolyte interfaces. Graphical Abstract: The O-Pd-Cl interfaces with high activity and CO tolerance is constructed in saturated KCl electrolyte for stable CO2 RR. The Cl - ions in electrolyte triggers the surface dynamic reconstruction of Pd/C catalyst during CO2 electrolysis. The constructed new micro-environments for water molecules in saturated KCl electrolyte also strongly inhibit hydrogen evolution reaction, thus achieving nearly 100% of CO selectivity. ga1 Highlights: The O-Pd-Cl interfaces with high activity and CO tolerance is constructed in saturated KCl electrolyte. The O-Pd-Cl interfaces can endure over 2000 and 20000 ppm CO in H-cell and flow cell, respectively. Using such highly concentrated saturated KCl electrolyte, the hydrogen evolution reaction is strongly suppressed. The reconstructed Pd/C catalyst in saturated KCl electrolyte achieves near 100% selectivity for CO production.